Pengaruh Woman On Board Room Terhadap Kinerja Perusahaan - Mahyuni, Sri; Rahmawati, Wulan (JURNAL MUTIARA AKUNTANSI, 2022)
This paper examines the relationship between woman in board and company performance.  Measurements of dependent and independent variables in this study, for company performance used ROA and ROE and for firm value by TobinsQ. Measurement of Women on Board (WOB) is measured based on the sum of the number of woman on the board of commissioners and board of directors divideb by the total number of boards. Measurement of WOB considered that Indonesia adheres to a Double tier system. In this study, differences in the composition of the number of women in the structure of the board of commissioners and the board of directors were carried out. This research is an association study that is tested by OLS regression by STATA Software. Using 3 listed company sectors on the IDX based on the Report In 2018, this study found that there was a significant negative effect on the relationship between the number of women in the board of commissioners and board of director’s structure on company performance.